2023
DOI: 10.3389/fped.2023.1261046
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of COVID-19 and influenza in hospitalized children <5 years in the US

Leah J. McGrath,
Mary M. Moran,
Tamuno Alfred
et al.

Abstract: IntroductionWe compared hospitalization outcomes of young children hospitalized with COVID-19 to those hospitalized with influenza in the United States.MethodsPatients aged 0-&lt;5 years hospitalized with an admission diagnosis of acute COVID-19 (April 2021-March 2022) or influenza (April 2019-March 2020) were selected from the PINC AI Healthcare Database Special Release. Hospitalization outcomes included length of stay (LOS), intensive care unit (ICU) admission, oxygen supplementation, and mechanical vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…(1216) Trends were similar, although with a narrower magnitude of difference, in pediatrics: longer length of stay, yet fewer children admitted to ICU or receiving IMV in Japan as compared to the US. (13,1721) Systematic reviews have previously reported regional differences similar to those outlined above. (22)…”
Section: Discussionmentioning
confidence: 69%
“…(1216) Trends were similar, although with a narrower magnitude of difference, in pediatrics: longer length of stay, yet fewer children admitted to ICU or receiving IMV in Japan as compared to the US. (13,1721) Systematic reviews have previously reported regional differences similar to those outlined above. (22)…”
Section: Discussionmentioning
confidence: 69%
“…This study used a retrospective cohort design to characterize hospitalization outcomes among children aged <5 years and hospitalized with COVID-19 ( 15 ). The data source was the nationally representative PINC AI™ (formerly Premier) Healthcare Database Special Edition (PHD SR), which covers approximately a quarter of all hospital admissions annually arising from ∼1,400 hospitals in the U.S.…”
Section: Methodsmentioning
confidence: 99%
“…Disease severity was based on the outcomes of interest which included length of stay (LOS), intensive care unit (ICU) admission, oxygen supplementation, invasive mechanical ventilatory (IMV) support, and prolonged duration of each outcome. Prolonged duration was defined as longer than the median value among all patients who experienced that outcome (>2 days for each outcome) ( 15 ).…”
Section: Methodsmentioning
confidence: 99%